Problem-Based Learning in Teaching English for Law Enforcement - PIELMUȘ, Cristina (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2026)
Problem-based learning (PBL) is a pedagogical approach used in second language acquisition to enable students to improve their critical thinking and social skills, while learning the target language in context by endeavoring to find solutions to real-life or job-related problems. In English language teaching (ELT), the PBL approach implies that students identify problems, design strategies, and also reflect on their resolution process, stages along which they interact with each other, thus further developing their language competencies. Our paper aims to showcase how this approach can be implemented in second language teaching in the context of law enforcement tertiary education.